Top Paper Award - Andreou, Panayiotis (My University, 2026)
The 28th Annual Global Finance Conference Virtual, May 27 - 28, 2021 Top Paper Award Stock Price Crash Risk: A critique of the Agency Theory Viewpoint Presented to:Panayiotis C. Andreou, Cyprus University of Technology
Keywords: Sciences